Possible and Impossible Harmony (Dialektika Islam-Kristen Di Durensewu Pandaan Pasuruan) - Huda, Thoriqul (Ali Muchasan, 2018)
Religious life in Indonesia still often experience ups and downs. Religion is sometimes still becoming the issue of igniting the conflict in the midst of social life. Despite, on the other hand, Religion teaches its people to be a good person. Basically, every individual has a responsibility to maintain harmony in the neighborhood as practiced by Muslims and Christians in Durensewu. The harmony between Islam and Christianity is beneficial that the social life is far from conflict. In establishing inter-religious relationships, there are several possible things between Muslim and Christians to cooperate and harmonize which is called possible harmony. However, in some ways, it is not possible to cooperate between Muslim-Christians, called impossible harmony.